2010
DOI: 10.1021/om100435x
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Bidentate Triazolyl-Functionalized N-Heterocyclic Carbenes and Their Palladium Complexes

Abstract: New heterobidentate N-heterocyclic carbene-triazolyl ligands and several of their palladium(II) complexes have been synthesized in a modular fashion using click chemistry. These complexes are the first examples where triazolyl-substituted NHCs exhibit bidentate behavior, which was confirmed by NMR and X-ray diffraction studies. The synthesis of the complexes could be achieved in relatively few steps by introducing the diversity at a late stage in the synthesis. The complexes are active precatalysts in the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 44 publications
2
51
0
1
Order By: Relevance
“…[5] A significant influence of the nitrogen donor on the activity and selectivity were found. [7] The results of our screening with differently substituted NHC-picolyl ligands are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] A significant influence of the nitrogen donor on the activity and selectivity were found. [7] The results of our screening with differently substituted NHC-picolyl ligands are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In previous publications, we have shown the effect of various nitrogen donors on the coordinative properties of the ligands and the catalytic activity and selectivity of their zero-and divalent palladium complexes. [5][6][7]26] The use of picoline as donor in combination with NHC ligands is also known, and the coordination chemistry of these flexible aromatic have been studied by NMR and X-ray diffraction, confirming their bidentate nature. The complexes are active precatalysts in the transfer semihydrogenation of alkynes to Z-alkenes, with activity and selectivity depending on the picolyl substituent to a high degree.…”
Section: Introductionmentioning
confidence: 96%
“…A saturated aqueous sodium EDTA solution (preferred) or saturated aqueous ammonium chloride solution was used to remove the copper catalyst. During the course of our studies, Elsevier et al 5 and Chen et al 6 reported the synthesis of a number of analogous imidazolium-1,2,3-triazole ligands with either Br or PF 6 − as the counter anion and their complexes with palladium. Ligand 1d with an aniline functional group (n = 1; R 2 = NH 2 , Scheme 1) was synthesised by the reduction of the corresponding nitro compound 1c with hydrazine hydrate in the presence of palladium on activated carbon.…”
Section: Synthesis Of Ligandsmentioning
confidence: 99%
“…There have been only two reports of late transition metal complexes containing mixed NHC-1,2,3-triazolyl bidentate ligands, and each of these reported the synthesis of palladium complexes. 5,6 More recently, Cowie and co-workers reported the synthesis of a number of imidazolium-1,2,3-triazolyl salts but then alkylated the 1,2,3-triazolyl moiety to triazolium. They † Electronic supplementary information (ESI) available: Syntheses and characterization of ligands 1b-c and 1e-g; Rh(I) complexes 2b-d and 3b-d; Rh(III) complexes 4b-d; Ir(III) complexes (5b-c).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown thatakinetically stable trans-isomer was obtained when two equivalents of NHC were coordinated to palladium [3].When only one equivalent is used, the dinuclear species is formed preferentially over thee xpectedm ononuclear species in which the ligand coordinates bidentate [4][5][6]. However, theamide does play arole, in contrast to earlier reports [3].…”
Section: Discussionmentioning
confidence: 81%